Positive-Mode-Damping Stability Criterion Application and Damping Solutions in Microgrid-Integrated Transmission Grids - Oriol Cartiel; Pablo Horrillo-Quintero; Juan-José Mesas; Pablo García-Triviño; Raúl Sarrias-Mena; Luis M. Fernández-Ramírez; Luis Sainz (Energies)
Stability problems are increasing in current power systems with a large number of electronic converters, such as microgrids (MGs) and microgrid clusters (MGCs). Frequency-domain methods, commonly used to analyse traditional power system stability, can also be extended to MGs. In particular, the positive-mode-damping (PMD) stability criterion is a simple and practical method to evaluate the stability of multi-terminal power electronics-based systems, making it a powerful tool for addressing stability issues in MGCs. This paper extends the application of the PMD stability criterion to assess stability in MGC-integrated transmission grids. Moreover, it presents two bandpass filter-based active and passive damping compensators and examines their effectiveness in mitigating instabilities in MGCs. A modified IEEE three-bus power system integrating an MGC is used to conduct a small-signal harmonic stability study and apply active and passive damping solutions with the PMD stability criterion. The modified IEEE three-bus power system is implemented in real-time simulations using a hardware-in-the-loop setup with OPAL-RT4512 to validate the results obtained from MATLAB/Simulink R2022a simulations.